Fostering the innovative work behavior of knowledge workers in Malaysia's knowledge intensive business services - A social capital perspective - Yeoh, Khar Kheng; June, Sethela (2014)
This study was conducted to investigate the relationship between social capital and innovative work behavior among the knowledge workers of the knowledge intensive business services in Malaysia.It was reported that social capital to have a significant relationship with innovative work behavior of employees in various business sectors. However, some researchers concluded the relationship is rather weak. A total of 1520 mail survey questionnaires was distributed and 310 deemed usable for analysis using SPSS, resulted in 20.6 % response rate. The results revealed that there was a significant relationship between social capitals and the innovative work behavior of knowledge workers.